Cell membrane-coated mRNA nanoparticles for enhanced delivery to dendritic cells and immunotherapy - Qiaoyun Li; Junho Byun; Dongyoon Kim; Yina Wu; Jaiwoo Lee; Yu-Kyoung Oh (Asian Journal of Pharmaceutical Sciences)
Cationic polymers such as polyethylenimine have been considered promising carriers for mRNA vaccines. However, their application is hindered by their inherent toxicity and a lack of targeted delivery capability. These issues need to be addressed to develop effective cancer vaccines. In this study, we investigated whether dendritic cell membrane-coated polyethylenimine/mRNA nanoparticles (DPN) could effectively deliver mRNA to dendritic cells and induce immune responses. For comparison, we employed red blood cell membrane-coated polyethylenimine/mRNA (RPN) and plain polyethylenimine/mRNA polyplex (PN). The dendritic cell membrane coating altered the zeta potential values and surface protein patterns of PN. DPN demonstrated significantly higher uptake in dendritic cells compared to PN and RPN, and it also showed greater mRNA expression within these cells. DPN, carrying mRNA encoding luciferase, enhanced green fluorescent protein, or ovalbumin (OVA), exhibited higher protein expression in dendritic cells than the other groups. Additionally, DPN exhibited favorable mRNA escape from lysosomes post-internalization into dendritic cells. In mice, subcutaneous administration of DPN containing ovalbumin mRNA (DPNOVA) elicited higher titers of anti-OVA IgG antibodies and a greater population of OVA-specific CD8+ T cells than the other groups. In a B16F10-OVA tumor model, DPNOVA treatment resulted in the lowest tumor growth among the treated groups. Moreover, the population of OVA-specific CD8+ T cells was the highest in the DPNOVA-treated group. While we demonstrated DPN's feasibility as an mRNA delivery system in a tumor model, the potential of DPN can be broadly extended for immunotherapeutic treatments of various diseases through mRNA delivery to antigen-presenting cells.